2016
DOI: 10.1208/s12249-016-0513-3
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Variation of Pressure in the Lyophilization Product Chamber Part 1: Computational Modeling

Abstract: The flow physics in the product chamber of a freeze dryer involves coupled heat and mass transfer at different length and time scales. The low-pressure environment and the relatively small flow velocities make it difficult to quantify the flow structure experimentally. The current work presents the three-dimensional computational fluid dynamics (CFD) modeling for vapor flow in a laboratory scale freeze dryer validated with experimental data and theory. The model accounts for the presence of a non-condensable g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…As proven by Trelea et al, this assumption works reasonably well when the condenser is separated from the drying chamber by a pipe, as for the equipment used for this study. Moreover, as confirmed by previous studies based on computational fluid dynamics simulations, , it is assumed that the variation of total pressure between the chamber and the condenser is negligible compared to the variation of water vapor partial pressure and that there are no significant pressure leaks in the chamber.…”
Section: Model Developmentmentioning
confidence: 78%
“…As proven by Trelea et al, this assumption works reasonably well when the condenser is separated from the drying chamber by a pipe, as for the equipment used for this study. Moreover, as confirmed by previous studies based on computational fluid dynamics simulations, , it is assumed that the variation of total pressure between the chamber and the condenser is negligible compared to the variation of water vapor partial pressure and that there are no significant pressure leaks in the chamber.…”
Section: Model Developmentmentioning
confidence: 78%
“…Conversely, the minimum chamber pressure is limited by the capability of the freeze-drying equipment. [31][32][33] In this sense, a PDS offers a method to identify the product and equipment limitations and to select the most optimized and robust process parameters for a given formulation.…”
Section: Cqasmentioning
confidence: 99%
“…The differences in freeze dryers can be observed by looking at the shelf temperature nonuniformity, refrigeration system, and duct resistance, which was investigated by Rambhatla et al 13 Computational modeling of the vapor flow in the freeze dryer can give not only the desired design parameters but also reveal the vapor flow patterns, the distribution of pressure as well as the relative concentration of water vapor, and noncondensable gases in the freeze dryer product chamber. Computational fluid dynamics (CFD) computations can explain the pressure variation in the chamber as investigated by Barresi et al 14 for pilot-scale freeze dryers and confirmed by comparison of CFD and experimental measurements for laboratory scale by Ganguly et al 15 Input from CFD can be used to design a process as done by Rasetto et al 16 Ganguly et al 17 investigated the amount of radiation, convection, and conduction for different vial arrangements and concluded that convection contribution to vial heat transfer can be significant. CFD can also be coupled with 1-D heat transfer equations to generated unsteady-state calculators for process design.…”
Section: Introductionmentioning
confidence: 70%